Understanding the differences in students' attitudes towards social media use: A case study from Oman - Al-Qaysi, Noor; Mohamad-Nordin, Norhisham; Al-Emran, Mostafa; Al-Sharafi, Mohammed A. (IEEE, 2019)
Social media use by university students attracted the interest of several scholars worldwide. However, a limited amount of research articles was published to investigate the students’ attitudes towards social media usage in the Arab world universities. As a case study, the core objective of this research is to measure the students’ attitudes towards the use of social media at an academic institute in Oman. The study intends to examine the differences in these attitudes from the lenses of several attributes, including gender, age, year of study, and social media application. A total of 198 students took part in the study through an online survey. Although the findings showed no significant differences in attitudes with regard to the aforementioned studied attributes, it is imperative to report that all the participated students were mutually interested in using social media applications in learning practices.